2004
DOI: 10.1016/j.polymer.2004.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of mechanical properties of clay filled polyamide mouldings with chromatographically measured surface energies

Abstract: Inverse gas chromatography, IGC, has been used to investigate the surface properties of calcined kaolins and the effect of the mechanical properties of a Nylon-6 composite containing the clay. Modification of the kaolin with an aminosilane coupling agent lowered its surface energy so that it was comparable with that of the polymer matrix and changed the surface from being acidic to being predominantly basic. The surface of the nylon was also found to be basic but susceptible to hydrogen bonding. Incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…IGC can be also used to analyze the solvent-solvent interactions [25], the surface properties of clays [26,27], nanomaterials and clay-polymer composites [28,29] and nanoparticles with respect to their specific surface area, particle size and morphology [30].…”
Section: Introductionmentioning
confidence: 99%
“…IGC can be also used to analyze the solvent-solvent interactions [25], the surface properties of clays [26,27], nanomaterials and clay-polymer composites [28,29] and nanoparticles with respect to their specific surface area, particle size and morphology [30].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the alkylammonium cations can provide functional groups that can react with the polymer to improve the strength of the interface between the inorganic component and the macromolecule. Inverse gas chromatography (IGC) has been used to investigate the surface properties of calcined kaolins and the effect on the mechanical properties of a nylon-6 composite containing the clay by Ansari and Price [8,9]. They believed that the modification of the kaolin with an aminosilane coupling agent lowered its surface energy so that it was comparable with that of the polymer matrix and changed the surface from being acidic to being predominantly basic.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still some hydroxyl functionality present so that a relatively high-energy surface remains. [3] The value of the dispersive component of surface energy for polymer was relatively low. As far as the organic/inorganic system is concerned, polystyrene was expected to minimize the surface energy of sepiolite as in the case of montmorillonite (MMT)-polystyrene sulfonate [16] and calcined kaolin-polyethylene.…”
Section: Resultsmentioning
confidence: 99%
“…By using probes with a range of properties, the nature of the surface can be defined with good accuracy. [3] Retention time is evaluated to be used in the calculations of some physicochemical properties of solids. Heat-treated natural clay was chosen in this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation